Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/12298093.2018.1514732
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of TwoChrysosporiumSpecies with Keratinolytic Activity from Field Soil in Korea

Abstract: In an ongoing survey of Korean indigenous fungi, two fungal strains (KNU16-74 and KNU16-99) belonging to the genus Chrysosporium were isolated from field soil in Gyeongnam, Korea. Morphological characterization and phylogenetic analysis using sequence of the internal transcribed spacer regions were carried out to confirm its precise identification. These strains were identified as Chrysosporium indicum (KNU16-74) and Chrysosporium fluviale (KNU16-99). To examine the keratin degradation efficiency of these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Azo-keratin Measuring absorbance at 450 nm Herzog et al, 2016;Gonzalo et al, 2020 Keratin azure Tork et al, 2013Tork et al, , 2016 Feather Measuring absorbance at 280 nm Bohacz and Korniłłowicz-Kowalska, 2019 Feather powder Fang et al, 2013;Qu et al, 2018 Cow horn Dozie et al, 1994 Wool top Iglesias et al, 2017 Recombinant feather keratin Jin et al, 2017 Human hair Measuring absorbance at 280 nm or using other reagents Lowry et al, 1951;Gurung et al, 2018 Azocasein Measuring absorbance at 366 nm Tork et al, 2013Tork et al, , 2016 Suc-Ala-Ala-Pro-Phe-pNA…”
Section: Substrate Assay Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Azo-keratin Measuring absorbance at 450 nm Herzog et al, 2016;Gonzalo et al, 2020 Keratin azure Tork et al, 2013Tork et al, , 2016 Feather Measuring absorbance at 280 nm Bohacz and Korniłłowicz-Kowalska, 2019 Feather powder Fang et al, 2013;Qu et al, 2018 Cow horn Dozie et al, 1994 Wool top Iglesias et al, 2017 Recombinant feather keratin Jin et al, 2017 Human hair Measuring absorbance at 280 nm or using other reagents Lowry et al, 1951;Gurung et al, 2018 Azocasein Measuring absorbance at 366 nm Tork et al, 2013Tork et al, , 2016 Suc-Ala-Ala-Pro-Phe-pNA…”
Section: Substrate Assay Referencesmentioning
confidence: 99%
“…Keratin-degrading fungi can be isolated from some tissues of human and animals as the produced keratinase might be important for the fungal infection ( Friedrich et al, 1999 ; Bohacz and Korniłłowicz-Kowalska, 2019 ; Zhang et al, 2019 ). It was shown that fungi such as Chrysosporium ( Bohacz, 2016 ; Gurung et al, 2018 ) and Trichophyton ( Zhang et al, 2019 ) were able to degrade keratins through their produced keratinases ( Shadzi et al, 2002 ; Hassan et al, 2020 ). Due to the function of keratins, keratinases in some pathogenic fungi might be essential for the invasion by breaking the barrier between the tissue and the environment.…”
Section: Mechanism Of Action For Keratinasementioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA of the strain TM237-S5 was isolated using a DNeasy Plant Mini Kit (Qiagen), according to the manufacturer's instructions. The ITS region was amplified with primers ITS1F (5 -CTTGGTCATTTAGAGGAAGTAA -3 ) and ITS4 (5 -TCCTCCGCTTATTGATATGC) using described polymerase chain reaction (PCR) conditions [36]. Amplicons were sequenced by Sanger sequencing (GATC, Eurofins genomics), and the sequences were aligned against the non-redundant database of the NCBI using the BLASTn program.…”
Section: Strain Isolation and Identificationmentioning
confidence: 99%
“…Amplicons were sequenced by Sanger sequencing (GATC, Eurofins genomics), and the sequences were aligned against the non-redundant database of the NCBI using the BLASTn program. Then, phylogeny inference was performed on the Phylogeny.fr platform and comprised the following steps [37]: Sequences from TM237-S5 and representative Chrysosporium and Chrysosporium-related sequences described by Gurung et al (2018) were aligned with MUSCLE (v3.8.31) [38]. After alignment, ambiguous regions were removed with Gblocks (v0.91b) [39].…”
Section: Strain Isolation and Identificationmentioning
confidence: 99%